Polyphosphate Synthetic Activity of Polyphosphate:AMP Phosphotransferase in Acinetobacter johnsonii 210A - Itoh, Hiromichi (American Society for Microbiology, 2004)
Polyphosphate:AMP phosphotransferase (PAP) has been identified as an enzyme that catalyzes the phosphorylation of AMP with inorganic polyphosphates [poly(P)] as phosphate donors. We found that the purified PAP of Acinetobacter johnsonii 210A has poly(P) synthetic activity. The PAP catalyzes the dephosphorylation of ADP and processively synthesizes poly(P) of 200 to 700 residues. Comparatively lower concentrations of MgCl(2) (20 mM) were required to obtain optimum poly(P) synthetic activity, whereas higher concentrations of MgCl(2) (100 mM) were necessary for optimum PAP activity. ADP is preferred over GDP as a phosphate donor for poly(P) synthesis. The K(m) and V(max) values for ADP in the poly(P) synthetic activity of PAP were 8.3 mM and 55 μmol min(−1) mg(−1), respectively. We concluded that the PAP of A. johnsonii 210A is a novel type of poly(P) kinase that uses ADP and GDP as substrates.